Multiple Trauma with Severe Brain Injury Cause by Impression Fracture : Case Report and Literature Review - Ahmad Hannan; Khamim Thohari; Khofifah Dwi Oktafiana; Mohammad Hasan; Muhammad Hanun Mahyudin (Universitas Muhammadiyah Semarang, 2023)
Background : Multiple trauma one of trauma caused by huge traumatic force involves many organs and tissues. AIS and ISS is scoring for multiple trauma diagnosis and classification. In this Case Report discuss about multiple trauma patient with Severe Brain Injury cause by Impression Fracture with open fracture in regio cruris sinistra and close fracture femur sinistra. Case presentation : The following is a case report of a 63-year-old female patient came to the emergency room of Soegiri Lamongan with decreased of consciousness due to a traffic accident. Mechanism of injury the patient's head hit the chair and the driver's side of the car pillar and the patient's legs were pinched by the car seat. Since 25-year-old patient has a history of uncontrolled diabetes mellitus but the patient regularly takes anti-diabetic drugs (OAD). Patient was diagnosed with multiple trauma with severe brain injury with suspected DAI with open fracture grade 3A middle 1/3 tibia and close fracture middle 1/3 distal femur.Conclusion : Multiple Trauma has a bad prognosis. The most important from Multiple trauma management is prehospotality management. Additional Severe Brain Injury make the diagnosis become worse.